Parentesen om det højre-reaktionære: Affolkningen møder flygtningestrømmen i det prekære liv - Ledstrup, Martin (K&K - Kultur og Klasse, 2018)
The new right in Europe is often associated with precarious life. But in this article, I show that cultural representations of Danish remote areas during the refugee crisis in 2015 and 2016 significantly complicates the relationship between rightist politics, precarity, and the stranger. With Lauren Berlant, I argue that the encounter between refugees and locals outside the city can be seen as an exemplary instance of the commons: a socially ambivalent situation of precarity where the refugee crisis is also transformed into a new kind of infrastructure. First, the article reviews precarity and the commons in contemporary theory. Second, the precarity of remoteness is in the feelings of abandonment, so while arriving refugees were cast in national media as the embodiment of crisis, I show that they were at the same time represented as a new opportunity for the remote area in Denmark. Lastly, I exemplify how the refugee crisis can also become an infrastructure for the literary imagination about remoteness, particularly in Nancy, Dennis Gade Kofods dystopic novel about the Danish island of Bornholm.